Comparison of live and dead molluscan assemblages suggests recent human-driven decline in benthic diversity in Phetchaburi (NW Gulf of Thailand). (1st December 2015) - Negri, Mauro Pietro; Sanfilippo, Rossana; Basso, Daniela; Rosso, Antonietta
Abstract: Dead and live molluscan assemblages from the coastal area of Phetchaburi (NW Gulf of Thailand) were compared by means of multivariate analysis. Seven thanatofacies were recognized, thriving in the area after the 1960s. Five of them, scattered along the tidal flat, represent oligotypic intertidal biotopes linked to a variety of environmental factors; the remaining two mirror high-diversity infralittoral associations. Conversely, only two poor, ill-defined biofacies thrive at present between the intertidal and the shallow infralittoral zones, somewhat resembling two of the thanatofacies. Diversity indexes reveal a dramatic biodiversity decline occurred from the 1960s onwards, far beyond the effects of time-averaging and accumulation. The responsibility for this reduction is largely attributable to the high impact of human activities, such as the intensive sea bottom trawling, the wastewaters from aquaculture (shrimp and fish ponds) and dense coastal villages, and, at a minor extent, the digging of edible molluscs from the tidal flat.